2015
DOI: 10.1097/shk.0000000000000268
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Overload in Patients With Severe Sepsis and Septic Shock Treated With Early Goal-Directed Therapy Is Associated With Increased Acute Need for Fluid-Related Medical Interventions and Hospital Death

Abstract: Early-goal-directed therapy (EGDT) consists of early, aggressive fluid resuscitation and is known to improve survival in sepsis. It is unknown how often EGDT leads to subsequent fluid overload and whether post-EGDT fluid overload affects patients’ outcomes. Our hypothesis was that septic patients treated with EGDT were at risk for fluid overload and that fluid overload would be associated with adverse outcomes. We conducted a retrospective cohort of 405 consecutive patients admitted with severe sepsis and sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
215
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(226 citation statements)
references
References 23 publications
4
215
2
5
Order By: Relevance
“…In 2011 Boyd and colleagues reported a mean fluid balance at 4 days of 11 6 8.9 L in a cohort of patients with septic shock (12), whereas 5 years earlier the European Sepsis Occurrence in Acutely Ill Patients study investigators reported a 72-hour mean fluid balance of 1.8 6 5 L (10). The authors of a recent single-center study reported a 44% prevalence of diuretic use in patients with clinical evidence of volume overload at Day 3 after admission for septic shock (9). Although there appears to be variability in practice over time, based on geographic location, and between studies, our results are within the range of what might be expected on the basis of previous reports.…”
Section: Comparison With Previous Studiessupporting
confidence: 67%
See 1 more Smart Citation
“…In 2011 Boyd and colleagues reported a mean fluid balance at 4 days of 11 6 8.9 L in a cohort of patients with septic shock (12), whereas 5 years earlier the European Sepsis Occurrence in Acutely Ill Patients study investigators reported a 72-hour mean fluid balance of 1.8 6 5 L (10). The authors of a recent single-center study reported a 44% prevalence of diuretic use in patients with clinical evidence of volume overload at Day 3 after admission for septic shock (9). Although there appears to be variability in practice over time, based on geographic location, and between studies, our results are within the range of what might be expected on the basis of previous reports.…”
Section: Comparison With Previous Studiessupporting
confidence: 67%
“…Several studies in patients with sepsis have shown an association between positive fluid balance or volume overload and mortality, acute kidney injury (AKI), or need for fluid-related interventions (9)(10)(11)(12)(13).…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study from Mayo Clinic, Kelm and colleagues demonstrated that the SSC approach to fluid resuscitation results in fluid overload in 67% of patients with fluid overload being an independent predictor of death with an odds ratio 1.92 (1.16-3.22) [11]. Acheampong and Vincent recently demonstrated that a large positive fluid balance starting on ICU day two was an independent predictor of death [12].…”
Section: Potential Dangersmentioning
confidence: 99%
“…False positive (e.g., patients testing positive for sepsis but actually not septic) will result in unnecessary resuscitation procedures, more antibiotic exposure, and higher cost. Extensive evidence shows that a persisting positive fluid balance is associated with adverse outcomes (51)(52)(53)(54)(55)(56). Therefore, inappropriate fluid management based on false positive results may create an unwarranted positive fluid balance with a corresponding higher mortality risk.…”
Section: Evidence From Observational Cohort Studiesmentioning
confidence: 99%